Doping‐Induced Amorphization, Vacancy, and Gradient Energy Band in SnS2 Nanosheet Arrays for Improved Photoelectrochemical Water Splitting. (9th April 2019) - Meng, Linxing; Wang, Siyu; Cao, Fengren; Tian, Wei; Long, Run; Li, Liang
Abstract: Photoelectrochemical (PEC) water splitting is a promising strategy to convert solar energy into hydrogen fuel. However, the poor bulk charge‐separation ability and slow surface oxygen evolution reaction (OER) dynamics of photoelectrodes impede the performance. We construct In‐ and Zn/In‐doped SnS2 nanosheet arrays through a hydrothermal method. The doping induces the simultaneous formation of an amorphous layer, S vacancies, and a gradient energy band. This leads to elevated carrier concentrations, an increased number of surface‐reaction sites, accelerated surface‐OER kinetics, and an enhanced bulk‐carrier separation efficiency with a decreased recombination rate. This efficient doping strategy allows to manipulate the morphology, crystallinity, and band structure of photoelectrodes for an improved PEC performance. Abstract : Hoch dotiert : In‐ und Zn/In‐dotierte SnS2 ‐Nanoschichten werden als Photoanoden in der photoelektrochemischen Wasserspaltung genutzt. Die Dotierung führt zur Bildung einer amorphen Schicht und S‐Leerstellen auf der Nanoschicht‐Oberfläche, außerdem führt sie einen Bandstrukturgradienten entlang des Querschnitts der Nanoschichten ein. Diese Effekte führen zu einer erhöhten Leistungsfähigkeit in der Wasserspaltung.